EEG in Late Infantile Neuronal Ceroid Lipofuscinosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The clinical and electroencephalographic findings in 18 cases (8 girls, 10 boys) with late infantile neuronal ceroid lipofuscinosis (NCL) are reported from the University of Genova, and University of Siena, Italy.